HATS-39b, HATS-40b, HATS-41b, and HATS-42b: three inflated hot Jupiters and a super-Jupiter transiting F stars. Issue 3 (20th March 2018) - Bento, J; Hartman, J D; Bakos, G Á; Bhatti, W; Csubry, Z; Penev, K; Bayliss, D; de Val-Borro, M; Zhou, G; Brahm, R; Espinoza, N; Rabus, M; et al.
Abstract: We report the discovery of four transiting hot Jupiters from the HATSouth survey: HATS-39b, HATS-40b, HATS-41b, and HATS-42b. These discoveries add to the growing number of transiting planets orbiting moderately bright (12.5 ≲ V ≲ 13.7) F dwarf stars on short (2-5 d) periods. The planets have similar radii, ranging from 1.33^+0.29_-0.20 R J for HATS-41b to 1.58^+0.16_-0.12 R J for HATS-40b. Their masses and bulk densities, however, span more than an order of magnitude. HATS-39b has a mass of 0.63 ± 0.13 M J, and an inflated radius of 1.57 ± 0.12 R J, making it a good target for future transmission spectroscopic studies. HATS-41b is a very massive 9.7 ± 1.6 M J planet and one of only a few hot Jupiters found to date with a mass over 5 M J . This planet orbits the highest metallicity star ([Fe/H] = 0.470 ± 0.010) known to host a transiting planet and is also likely on an eccentric orbit. The high mass, coupled with a relatively young age (1.34^+0.31_-0.51 Gyr) for the host star, is a factor that may explain why this planet's orbit has not yet circularized.